1)
x-y=6
x=6+y 6+у+6у+у^2=-4
у^2+7у+10=0
у1= -2
у2= 5
х1= 6+2= 8
х2= 6-5 = 1
ответ: (8; -2) ; (1;5)
5)
у-х+3=0
-х=-3-у
х= 3-у 3-у-1=y^2
-у^2-у+2=0
y^2+y-2=0
y1= 1
y2= -2
x1= 3-1 = 2
x2= 3+2 = 5
ответ: (2;1) ; (5;-2)
3)
x-y=1
-y=1-x
y= x-1 x^2-2x+2-26=0
x^2-2x-24=0
x1= 6
x2= -4
y1= 6-1 = 5
y2= -4-1 = -1
ответ: (6;5) ; (-4; -1)
2х*6 +5*6 =78
12х +30=78
12х=78-30
12х=48
х=48/12
х=4
проверим:
(2*4+5)*6=78
13*6=78
78=78
(3х-10)*4=20
3х-10=20:4
3х-10=5
3х=5+10
х=15:3
х=5
проверим:
(3*5-10)*4=20
5*4=20
20=20
(2х-9):5=3
2х-9=3*5
2х=15+9
2х=24
х=24:2
х=12
проверим:
(2*12-9):5=3
(24-9):5=3
15:5=3
3=3
(7х+3):6=4
7х+3=4*6
7х=24-3
7х=21
х=21:7
х=3
проверим:
(7*3+3):6=4
24:6=4
4=4
(10х-27)*5 = 15
10х-27= 15:5
10х -27=3
10х=3+27
х=30:10
х=3
проверим:
(10*3-27)*5=15
(30-27)*5=15
3*5=15
15=15
(8х+3):7=5
8х+3=5*7
8х+3=35
8х=35-3
8х=32
х=32:8
х=4
проверим:
(8*4+3):7=5
35:7=5
5=5